2019
DOI: 10.1039/c9tc03838h
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation-induced emission triggered by the radiative-transition-switch of a cyclometallated Pt(ii) complex

Abstract: A new mechanism, namely radiative transition switch (RTS), has been proposed for aggregation-induced emission, which is of importance for developing highly efficient AIE-active emitters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The thermal gravimetric analysis revealed that the decomposition temperatures (T d ) of PyDPt, PmDPt, ThDPt, and QuDPt were 327, 273, 318, and 292 °C, respectively (Figure S4). At present, it is unclear why the pyrimidine-based dinuclear Pt(II) complex PmDPt had a slightly lower decomposition temperature, but this phenomenon is consistent with that recorded for corresponding mononuclear Pt(II) complexes (DPA-Pt: 43 T d = 263 °C; Pt-Py: 44 T d = 290 °C). Nevertheless, PyDPt, ThDPt, and QuDPt showed high T d close to or higher than 300 °C, indicating their good thermal stabilities.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The thermal gravimetric analysis revealed that the decomposition temperatures (T d ) of PyDPt, PmDPt, ThDPt, and QuDPt were 327, 273, 318, and 292 °C, respectively (Figure S4). At present, it is unclear why the pyrimidine-based dinuclear Pt(II) complex PmDPt had a slightly lower decomposition temperature, but this phenomenon is consistent with that recorded for corresponding mononuclear Pt(II) complexes (DPA-Pt: 43 T d = 263 °C; Pt-Py: 44 T d = 290 °C). Nevertheless, PyDPt, ThDPt, and QuDPt showed high T d close to or higher than 300 °C, indicating their good thermal stabilities.…”
Section: Resultssupporting
confidence: 75%
“…Compared with the PLQYs of the triphenylamine-based mononuclear Pt(II) complexes Pt-Py (PLQY = 0.07) 44 and DPA-Pt (PLQY = 0.03) 43 in CH 2 Cl 2 at room temperature, the PLQYs of these dinuclear Pt(II) complexes notably increased to 0.11−0.22. The improvement of emission efficiencies was temporarily attributed to the enhanced ISC due to the incorporation of the second Pt center.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Since the pioneering report by Tang and co-workers, molecular materials with aggregation-induced or enhanced emissions (AIE or AEE) have aroused widespread interest. , Most of the current works focus on luminescent AIE/AEE materials. Purely organic chromophores or transitional metal complexes, including platinum complexes, have been documented to show aggregation-induced or -enhanced phosphorescent emission (AIPE or AEPE) with potential applications in light-emitting devices, information encryption, and bioimaging. However, the scope of AIPE/AEPE materials remains to be expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Molecules are individual building blocks, and the way in which they organize has a great impact on their chemical and physical properties. Based on the interacting molecules, cation−π interactions, anion−π interactions, lone pair interactions, CH···π interactions, π–π stacking interactions, , and metallophilic interactions have emerged as driving intermolecular forces in aggregated structures. In other scenarios, nondirectional hydrophobic (i.e., dispersion-driven) interactions drive the formation of molecular aggregates .…”
Section: Introductionmentioning
confidence: 99%